Prototype MIMO Transmitter for Spin Stabilized Vehicles - Eckler, Kyle (International Foundation for Telemetering, 2011)
ITC/USA 2011 Conference Proceedings / The Forty-Seventh Annual International Telemetering Conference and Technical Exhibition / October 24-27, 2011 / Bally's Las Vegas, Las Vegas, Nevada === This paper describes the design of an inexpensive and scalable transmitter for a Multiple-Input Multiple-Output (MIMO) communication system. The transmitter is intended to be used in aerospace applications, especially in spin stabilized vehicles. A field programmable gate array (FPGA) in the modulator will implement a modified Alamouti space time block code which will take advantage of the cyclostationary nature of the channel to increase the system data rate.